2014
DOI: 10.1364/ol.39.006013
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved multifocal multiphoton microscope for high speed FRET imaging in vivo

Abstract: Imaging the spatiotemporal interaction of proteins in vivo is essential to understanding the complexities of biological systems. The highest accuracy monitoring of protein-protein interactions is achieved using Förster resonance energy transfer (FRET) measured by fluorescence lifetime imaging, with measurements taking minutes to acquire a single frame, limiting their use in dynamic live cell systems. We present a diffraction limited, massively parallel, time-resolved multifocal multiphoton microscope capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…These SPAD arrays hold great promise for the advancement of time-resolved fluorescence microscopy, but they currently have a low fill factor and much higher noise levels than MCP-based detectors. The current low fill factor of well below 10% makes their use as cameras for direct FLIM imaging inefficient unless this drawback is overcome, for example with microlenses or multifocal multibeam scanning approaches [69]. The dark noise performance of SPAD arrays, typically hundreds of counts per pixel SPAD, depending on the operating voltage and temperature [8], can be improved to tens of counts per pixel (25 Hz has been quoted [70]) but it is still many orders of magnitude higher than MCP-based intensifiers, for which 0.02 events s −1 cm −2 have been quoted [71].…”
Section: Discussionmentioning
confidence: 99%
“…These SPAD arrays hold great promise for the advancement of time-resolved fluorescence microscopy, but they currently have a low fill factor and much higher noise levels than MCP-based detectors. The current low fill factor of well below 10% makes their use as cameras for direct FLIM imaging inefficient unless this drawback is overcome, for example with microlenses or multifocal multibeam scanning approaches [69]. The dark noise performance of SPAD arrays, typically hundreds of counts per pixel SPAD, depending on the operating voltage and temperature [8], can be improved to tens of counts per pixel (25 Hz has been quoted [70]) but it is still many orders of magnitude higher than MCP-based intensifiers, for which 0.02 events s −1 cm −2 have been quoted [71].…”
Section: Discussionmentioning
confidence: 99%
“…The use of microlens arrays is a possible solution but may be impractical for this task. However, preliminary multifocal multibeam approaches (Poland et al, 2014a,b) have been successfully demonstrated to achieve this aim (Colyer et al, 2010;Poland et al, 2013Poland et al, , 2014a. Promising current developments in 3D stacking of integrated circuits (Garrou et al, 2011) will ensure a fill factor >80%, a better time resolution and reduced jitter.…”
Section: Spad Arraysmentioning
confidence: 99%
“…Several recent advances in MP microscopy have provided improved acquisition speeds for FLIM-based approaches (Kirkpatrick et al, 2012;Rinnenthal et al, 2013;Poland et al, 2014). Additionally, commercially available enhancements to microscopy are now available, including gallium arsenide phosphide multidetector units, which have higher quantum efficiency and wavelength sensitivity while still enabling lownoise high-speed imaging.…”
Section: Detecting Ret Sensors In Living Organismsmentioning
confidence: 99%